Mitochondrial Band-7 family proteins: scaffolds for respiratory chain assembly? - Gehl, Bernadette; Sweetlove, Lee J. (Frontiers in Plant Science, 2014)
The band-7 protein family comprises a diverse set of membrane-bound proteins characterised by the presence of a conserved domain. The exact function of this band-7 domain remains elusive, but examples from animal and bacterial stomatin-type proteins demonstrate binding to lipids and the ability to assemble into membrane-bound oligomers that form putative scaffolds. Some members, such as prohibitins and human stomatin-like protein 2 (HsSLP2), localise to the mitochondrial inner membrane where they function in cristae formation and hyperfusion. In Arabidopsis, the band-7 protein family has diversified and includes plant-specific members. Mitochondrial-localised members include prohibitins (AtPHBs) and two stomatin-like proteins (AtSLP1 and -2). Studies into PHB function in plants have demonstrated an involvement in root meristem proliferation and putative scaffold formation for mAAA proteases, but it remains unknown how these roles are achieved at the molecular level. In this minireview we summarise the current status of band-7 protein functions in Arabidopsis, and speculate how the mitochondrial members might recruit specific lipids to form microdomains that could shape the organisation and functioning of the respiratory chain.